Importance of rice research and development in rice seed policies: Insights from Nigeria - Takeshima, Hiroyuki (International Food Policy Research Institute, 2014)
First, this paper shows that rice varietal development in Nigeria has been lagging behind that of other developing countries in Asia and Latin America, due partly to insufficient investment in domestic rice R&D. The paper then illustrates using a household model simulation that impacts of certain policies, such as the seed subsidy, may be greater (smaller) if they are applied to good (poor) varieties. The paper concludes by discussing key policy implications and future research needs.